KARYOTYPIC ANALYSIS AND CHROMOSOME BIOMETRY OF CELL-CULTURES OF THE YELLOW-THROATED ALLIGATOR (CAIMAN-LATIROSTRIS DAUDIN) - Lui, J. F.; Valencia, EFT; Boer, J. A. (Soc Brasil Genetica, 1994)
Blood from eight specimens of both sexes of the alligator Caiman latirostris was collected and incubated in culture medium. Conventional as well as chromosomal banding (C and NOR) techniques were used.The diploid number was determined as 42, being 24 telocentric, 12 metacentric and six submetacentric, with real lengths varying from 1.49 to 6.08, 1.63 to 3.71, and 2.41 to 3.19 mum, respectively. The fundamental number was 60. About 81% of the chromosomes were small and 19% medium in size. NOR-banding was presented for the first time for this species and it was verified that only one submetacentric pair (no. 20) was marked on arm q, and under conventional staining it presented a secondary constriction. There was no association between NOR marked chromosomes.